2007
DOI: 10.1634/stemcells.2007-0022
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Support Migration, Extracellular Matrix Invasion, Proliferation, and Survival of Endothelial Cells In Vitro

Abstract: We investigated effects of the paracrine factors secreted by human mesenchymal stem cells (hMSCs) on endothelial cell migration, extracellular matrix invasion, proliferation, and survival in vitro. Human mesenchymal stem cells were cultured as a monolayer or as three-dimensional aggregates in hanging drops (hMSC spheroids). We performed analysis of paracrine factors in medium conditioned by a monolayer of hMSCs and hMSC spheroids. Concentrations of vascular endothelial growth factor (VEGF), basic fibroblast gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
229
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 284 publications
(256 citation statements)
references
References 19 publications
(36 reference statements)
14
229
2
Order By: Relevance
“…While there were differences in gene expression patterns, these did not generally overlap with previous reports that had conducted similar gene expression surveys [327,328]. This lack of consistency between our current study and previous reports suggested that there were higher order variables that dominated over the influences driven by 2D versus 3D cell culture geometry.…”
Section: Resultssupporting
confidence: 58%
See 4 more Smart Citations
“…While there were differences in gene expression patterns, these did not generally overlap with previous reports that had conducted similar gene expression surveys [327,328]. This lack of consistency between our current study and previous reports suggested that there were higher order variables that dominated over the influences driven by 2D versus 3D cell culture geometry.…”
Section: Resultssupporting
confidence: 58%
“…In Table 2.2, a number of differentially expressed genes were contrasted from the current study (red heading) and those reported by Potapova et al [327] (green heading), against those reported to be significantly up--regulated by Bartosh et al [328] (blue heading).…”
Section: Msc 2d and 3d Gene Expression Analysis Using Microarraysmentioning
confidence: 75%
See 3 more Smart Citations